PERAN GURU GARIS DEPAN DALAM MENGEMBANGKAN SEKOLAH EFEKTIF - Rahmi Rivalina (Perspektif Ilmu Pendidikan, 2016)
The problem discussed in this study is improving the roles of frontlined teachers (GGD) in developing the schools they assigned to become an Effective School. This study aims at contributing a thought for improving the roles of frontlined teachers in developing the school they assigned to become Effective School in East Aceh. The method used was a descriptive qualitative by applying data collecting technique such as interview, Focus Group Discussion (FGD), documentary, and observation conducted through December 2015. The study reveals some roles of the frontlined teachers are to be optimalized related to (1) school principal, (2) fellow teachers, (3) students, (4) parents/community, and (5) fellow frontlined teachers,. The conclusion of this study is that the presence of frontlined teachers is needed to help overcome the educational school problems in East Aceh Disrict.